Advertising in Contemporary Consumer Culture - de Burgh-Woodman, Hélène (Springer International Publishing, 2018)
This is the first scholarly book dedicated to reading the work of contemporary filmmakers and their impact on modern marketing and advertising. Drawing from consumer culture theory, film and media studies, the author presents an expansive analysis of a range of renowned filmmakers who have successfully applied their aesthetic and narrative vision to commercial advertising. It challenges some traditional advertising tropes and sheds light on the changing nature of advertising in the contemporary media context. Utilising Deleuze and Guattari's notion of assemblage, this book addresses themes of spatiality and time, narrative and aesthetics and consumer reception within a new frame of reference that re-contextualises classical concepts of genre, platform and aesthetic categories. These diverse elements are embedded into a larger discussion of the resonance of contemporary advertising for consumer culture and the implications of the hybridity characteristic of convergent media platforms for understanding the potential of advertising in the twenty-first century. It offers a cutting-edge, interdisciplinary perspective for researchers, academics, and practitioners working in marketing communications, advertising, and media studies.